Home to Harmony - Gulley, Philip (Philip Gulley). (New York : HarperCollins, 2008)
Come home to Harmony, Indiana, a peaceful slice of small-town America, as Sam Gardner, Harmony-born and raised, begins his inaugural year as pastor to a new flock of old friends, family members, and outrageous eccentrics -- in this unforgettable place where earth-shattering events rarely occur, but small life-altering ones happen daily.
Title from eBook information screen.
Electronic reproduction.
Requires Adobe Digital Editions (file size: 1137 KB) or Mobipocket Reader (file size: 253 KB).
Keywords: Fiction; Literature; Electronic books